2021
DOI: 10.1088/1742-6596/1899/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities Test of Ethanol Extracts of Kundur Fruit (Benincasa hispida Thunb. Cogn) on Salmonella typhi Bacteria

Abstract: One of the natural ingredients that can be used as medicinal plants is kundur fruit (Benincasa hispida Thunb. Cogn). Kundur is one of the plants that contain compounds that are efficacious in medicine. The people of the Moronene tribe in Southeast Sulawesi used to consume kundur fruit in a shredded way to treat typhoid caused by bacterium Salmonella typhi (S. Typhi). The general objective of this study was to determine the bioactivity of the ethanol extract of kundur fruit (B. hispida) as an antibacterial S. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The results obtained showed that the largest percentage of extract amendments in Kayu banana unripe fruit extract was 18.7 % and close to Kayu banana unripe fruit peel extract by 18.52 %. The difference in the percent yield obtained is influenced by the amount of organic solvent, the characteristics of the content of secondary metabolite compounds and the extraction method used [20]. Based on phytochemical screening carried out, the compounds contained in unripe fruit extracts and unripe fruit peel extracts of banana Kayu are alkaloids, flavonoids, saponins, tannins, triterpenoids, polyphenols and anthraquinones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained showed that the largest percentage of extract amendments in Kayu banana unripe fruit extract was 18.7 % and close to Kayu banana unripe fruit peel extract by 18.52 %. The difference in the percent yield obtained is influenced by the amount of organic solvent, the characteristics of the content of secondary metabolite compounds and the extraction method used [20]. Based on phytochemical screening carried out, the compounds contained in unripe fruit extracts and unripe fruit peel extracts of banana Kayu are alkaloids, flavonoids, saponins, tannins, triterpenoids, polyphenols and anthraquinones.…”
Section: Resultsmentioning
confidence: 99%
“…Storage of simplicia that has become a powder is carried out by putting the fine simplisia into a tightly closed container and tightly closed to avoid exposure to sunlight or insect ingress and giving silica gel to absorb moisture [29]. The difference in the percent yield obtained is influenced by the amount of organic solvent, the characteristics of the content of secondary metabolite compounds and the extraction method used [20]. The unripe fruit flesh extract of the Kayu banana contains alkaloid compounds, saponins, tannins, triterpenoids and polyphenols [34,35].…”
Section: Resultsmentioning
confidence: 99%
“…Salmonella typhimurium resides in the gastrointestinal system (small digestive tract) of humans and animals. The ideal temperature for the development of Salmonella typhimurium is 37°C, and it thrives at a pH of 6-8 (Supiati, 2022).…”
Section: The Effect Of Combined Administration Of Sea Urchin Gonad An...mentioning
confidence: 99%